The clinician impact and financial cost to the NHS of litigation over pregabalin: a cohort study in English primary care - Croker, R; Smyth, D; Walker, A; Goldacre, B (BMJ Publishing Group, 2018)
Following litigation over pregabalin's second-use medical patent for neuropathic pain, National Health Service (NHS) England was required by the court to instruct general practitioners (GPs) to prescribe the branded form (Lyrica) for pain. Pfizer's patent was found invalid in 2015, a ruling subject to ongoing appeals. If the Supreme Court appeal in February 2018, whose judgement is awaited, is unsuccessful, the NHS can seek to reclaim excess prescribing costs. We set out to describe the variation in prescribing of pregabalin as branded Lyrica, geographically and over time; to determine how clinicians responded to the NHS England instruction to GPs; and to model excess costs to the NHS attributable to the legal judgements.English primary care.English general practices.Variation in prescribing of branded Lyrica across the country before and after the NHS England instruction, by practice and by Clinical Commissioning Group; excess prescribing costs.The proportion of pregabalin prescribed as Lyrica increased from 0.3% over 6 months before the NHS England instruction (September 2014 to February 2015) to 25.7% afterwards (April to September 2015). Although 70% of pregabalin is estimated to be for pain, including neuropathic pain, only 11.6% of practices prescribed Lyrica at this level; the median proportion prescribed as Lyrica was 8.8% (IQR 1.1%-41.9%). If pregabalin had come entirely off patent in September 2015, and Pfizer had not appealed, we estimate the NHS would have spent £502 million less on pregabalin to July 2017.NHS England instructions to GPs regarding branded prescription of pregabalin were widely ignored and have created much debate around clinical independence in prescribing. Protecting revenue from 'skinny labels' will pose a challenge. If Pfizer's final appeal on the patent is unsuccessful, the NHS can seek reimbursement of excess pregabalin prescribing costs, potentially £502 million.